2023
DOI: 10.3390/medicina59101769
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Male Infertility: The Protective Role of Antioxidants

Aris Kaltsas

Abstract: Oxidative stress is a significant factor in male infertility, compromising sperm function and overall reproductive health. As male infertility garners increasing attention, effective therapeutic interventions become paramount. This review investigates the therapeutic role of antioxidants in addressing male infertility. A detailed examination was conducted on antioxidants such as vitamin C, E, B12, D, coenzyme Q10, zinc, folic acid, selenium, l-carnitine, l-arginine, inositols, and alpha-lipoic acid. This analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 243 publications
(311 reference statements)
0
6
0
Order By: Relevance
“…Regarding the varicocele condition, the percentage of patients with varicocele grade Therefore, this study demonstrates that daily supplementation of Spermotrend for a continuous period of 6 months has a beneficial effect on sperm quality and the control of venous flow and dilation associated with varicocele, despite the heterogeneity of altered parameters associated with male infertility. The antioxidants and micronutrients of Spermotrend ® help restore proper REDOX balance and sperm metabolism, thus promoting the correct sperm morphology, motility, mobility, and maturation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the varicocele condition, the percentage of patients with varicocele grade Therefore, this study demonstrates that daily supplementation of Spermotrend for a continuous period of 6 months has a beneficial effect on sperm quality and the control of venous flow and dilation associated with varicocele, despite the heterogeneity of altered parameters associated with male infertility. The antioxidants and micronutrients of Spermotrend ® help restore proper REDOX balance and sperm metabolism, thus promoting the correct sperm morphology, motility, mobility, and maturation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence has demonstrated that an imbalance between free radical generation and antioxidant defense capacity in the testes and epididymis of rats may signify sexual dysfunction (Aitken & Roman, 2008;Finelli et al, 2022;Kaltsas, 2023). Reactive oxygen species, particularly superoxides, play a central role in the impairment of erectile function within cavernosal tissues (Agarwal et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive oxidative stress is one of the mechanisms responsible for male infertility [ 29 , 30 , 31 ]. It damages spermatozoan activities and male fertility.…”
Section: Discussionmentioning
confidence: 99%